2021
DOI: 10.1093/aob/mcab127
|View full text |Cite
|
Sign up to set email alerts
|

The moss traits that rule cyanobacterial colonization

Abstract: Background and Aims Cyanobacteria associated with mosses represent a main nitrogen (N) source in pristine, high latitude and altitude ecosystems due to their ability to fix N2. However, despite progress made regarding moss-cyanobacteria association, the factors driving the large interspecific variation in N2 fixation activity between moss species remain elusive. The aim of the study was to identify the traits of mosses that determine cyanobacterial colonization and thus, N2 fixation activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 48 publications
2
16
0
Order By: Relevance
“…These functional traits could lead to host‐specific micro‐habitat conditions and affect light and water availability to cyanobacteria colonies on moss leaves. Recently, Liu and Rousk (2021) showed that the moss hydration rate, which was related to species morphology, was a key trait controlling N 2 ‐fixation and cyanobacterial colonization on feather moss leaves. The link between moss identity and N 2 ‐fixation could also result from the structure of the moss microbiome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These functional traits could lead to host‐specific micro‐habitat conditions and affect light and water availability to cyanobacteria colonies on moss leaves. Recently, Liu and Rousk (2021) showed that the moss hydration rate, which was related to species morphology, was a key trait controlling N 2 ‐fixation and cyanobacterial colonization on feather moss leaves. The link between moss identity and N 2 ‐fixation could also result from the structure of the moss microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Liu and Rousk (2021) showed that the moss hydration rate, which was related to species morphology, was a key trait controlling N 2 -fixation and cyanobacterial colonization on feather moss leaves.…”
Section: Moss Identity Is a Major Driver Of Cyanobacterial Biomass An...mentioning
confidence: 99%
“…All moss species harbour cyanobacteria, albeit to a varying extent. This is reflected in a large range of N 2 fixation rates reported for mosses, and in the biomass of the cyanobacterial colonizers that usually scales well with N 2 fixation activity (Liu & Rousk, 2021). While abiotic factors such as nutrient availability and climate impact N 2 fixation associated with mosses (see below), N 2 fixation activity in mosses growing in the same habitat can differ many fold (Calabria et al ., 2020; Jean et al ., 2020; Stuart et al ., 2021).…”
Section: The Players: Biotic Controlsmentioning
confidence: 99%
“…However, none of the liverworts assessed in this study belong to genera already known to form ‘true’ symbioses with diazotrophs (Adams & Duggan, 2008). Specific bryophyte traits are a driving factor of associated N 2 fixation, for example, by controlling bryophyte moisture level and thereby diazotroph colonization and activity (Liu & Rousk, 2021). The liverwort associated with the highest N 2 fixing activity in our study, Herbertus sp., is a ‘leafy’ liverwort, with morphology similar to mosses in terms of size and structure, separated into stem and leaves, which could explain the similar high N 2 fixation activity associated with this liverwort species.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen fixation activity of bacteria hosted by bryophytes is affected by abiotic factors such as temperature and moisture availability (Cusack et al, 2009; Gundale, Nilsson, et al, 2012; Permin et al, 2022; Rousk, Jones, et al, 2013), with desiccation inhibiting activity (Rousk et al, 2014). Also increased N availability can inhibit N 2 fixation in mosses (Rousk, Rousk, et al, 2013; Wang et al, 2021) and moss pH can affect N 2 fixation activity (Alvarenga & Rousk, 2021; Liu & Rousk, 2021). Furthermore, specific morphology traits linked to bryophyte hydration rate (e.g.…”
Section: Introductionmentioning
confidence: 99%